Empowering Indigenous-led contaminant monitoring through collaborative partnerships and two-way capacity sharing - Louise Mercer; Deva-Lynn Pokiak; Dustin Whalen; Michael Lim; Paul J. Mann (Arctic Science)
Climate-driven landscape change, legacy waste, and ongoing infrastructural investment are leading to concerns about contaminant release in Arctic Indigenous and Local communities. Sustainable development that considers threats posed by accelerating environmental change requires accessible, appropriate, and sustained environmental data to inform strategic decision-making. Collaborative partnerships and capacity sharing are necessary to promote resilient and sustainable environmental monitoring approaches; however, effective collaboration has been hindered by mismatches in priorities and timelines between communities and research programs. We outline the development and later evolution of a community-based environmental research program focused on monitoring contamination threats posed by legacy infrastructure sourced from industry, transportation, and domestic waste sites. Capacities and insights from diverse knowledge systems guided each stage of our research approach. Reflections provided by an Indigenous and non-Indigenous Early Career Researcher share insights into different aspects of the research process. We highlight how cross-cultural partnerships and capacity sharing have enabled evolving and reflexive community-based contaminant monitoring. Our approach facilitates a structural shift from collaborative monitoring with external analysis to autonomous monitoring that supports equity in research outcomes. Appropriately considered and resourced co-development at regular points of the research process has been critical to developing a complete and effective Indigenous-led research project.